Development of a Model to Predict Portal Vein Thrombosis in Liver Transplant Candidates: The Portal Vein Thrombosis Risk Index. Issue 12 (19th September 2019) - Gaballa, Daniel; Bezinover, Dmitri; Kadry, Zakiyah; Eyster, Elaine; Wang, Ming; Northup, Patrick G.; Stine, Jonathan G.
Abstract : Portal vein thrombosis (PVT) is associated with inferior pretransplantation and posttransplantation outcomes. We aimed to create a predictive model to risk stratify transplant candidates for PVT. Data on adult transplants in the United States during the Model for End‐Stage Liver Disease (MELD) era through September 2016 were reviewed. We constructed and validated a scoring system composed of routine, readily available clinical information to predict the development of incident PVT at 12 months from transplantation listing. A total of 66, 568 liver transplant candidates were dichotomized into 2 groups to construct (n = 34, 751) and validate (n = 31, 817) a scoring system. In general, the derivation and validation cohorts were clinically similar. Although nonalcoholic steatohepatitis was a significant predictor of incident PVT (hazard ratio, 1.29; 95% confidence interval, 1.08‐1.54; P < 0.001), age, MELD score, and moderate‐to‐severe ascites were also associated with increased risk. African American race was associated with decreased risk. A scoring system (PVT risk index [RI]) of these 5 variables had an area under the curve of 0.71 and 0.70 in both derivation and validation cohorts, respectively. By applying the low cutoff score of 2.6, incident PVT could be accurately excluded (negative predictive value 94%). Using the high cutoff score of 4.6 (positive predictive value 85%), PVT could be diagnosed with high accuracy. The PVT‐RI predicts which candidates awaiting lifesaving liver transplantation will and will not develop future PVT. Although this scoring system will require prospective validation, it provides a powerful new tool for the clinician when risk stratifying cirrhosis patients prior to liver transplantation for future PVT development.